Family business in family ownership portfolios. (7th April 2010) - Rautiainen, Marita; Pihkala, Timo; Ikavalko, Markku
In this paper, we study family business portfolios and illustrate ownership that connects family and business systems. Traditional family business research has assumed the one family/one business concept to be the main model. This study builds on the ideas of modern portfolio theory and behavioural finance theory and suggests that the portfolio evaluation criteria of risk and return coexist with the basic family-based evaluation criteria of obligation, securing succession, or family unity. This longitudinal case study and case analysis suggest that the family can be seen as a viable governor for the business portfolio and that the family portfolio development can be characterised by the complex set of portfolio evaluation criteria, including the needs of the individual family members to the contingent needs of the distinct businesses. The paper concludes with a redefined collection of portfolio management criteria identified and suggestions for further research on the subject.